2021
DOI: 10.1101/2021.09.09.21262448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Analysis of SARS-CoV-2 Vaccine Breakthrough Infections and Associated Clinical Outcomes

Abstract: Understanding the rate and clinical features associated with vaccine breakthrough infections (VBT) is of critical public health importance. Recent evidence on VBT in Barnstable County, Massachusetts, has prompted guidance on masking for vaccinated individuals in areas of high community-level transmission. Additional data is needed to better understand the prevalence and rate of VBT infections. Using detailed disease investigation data from Washoe County, Nevada we sought to assess the rate of symptomatic infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Evidence from 25 studies from the previous review (Acharya et al 2021, Chia et al 2021, Christensen et al 2022, Elliott et al 2021, Eyre et al 2022, Griffin et al 2021, Hirotsu et al 2021, Hsu et al 2021, Kale et al 2021, Kang et al 2022, Kerwin et al 2021, Kislaya et al 2022b, Levine-Tiefenbrun et al 2021a, Levine-Tiefenbrun et al 2022, Luo et al 2021a, Lyngse et al 2022b, Magalis et al 2021, Pouwels et al 2021, Puhach et al 2022, Riemersma et al 2021, Salvatore et al 2021, Servellita et al 2022, Siddle et al 2022, Singanayagam et al 2021, Yi et al 2022 suggests mixed evidence for a difference in viral load between fully vaccinated and unvaccinated cases, with 17 studies suggesting no difference and 8 studies suggesting higher Ct values (lower viral load) in fully vaccinated cases.…”
Section: Viral Load (Ct Values)mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from 25 studies from the previous review (Acharya et al 2021, Chia et al 2021, Christensen et al 2022, Elliott et al 2021, Eyre et al 2022, Griffin et al 2021, Hirotsu et al 2021, Hsu et al 2021, Kale et al 2021, Kang et al 2022, Kerwin et al 2021, Kislaya et al 2022b, Levine-Tiefenbrun et al 2021a, Levine-Tiefenbrun et al 2022, Luo et al 2021a, Lyngse et al 2022b, Magalis et al 2021, Pouwels et al 2021, Puhach et al 2022, Riemersma et al 2021, Salvatore et al 2021, Servellita et al 2022, Siddle et al 2022, Singanayagam et al 2021, Yi et al 2022 suggests mixed evidence for a difference in viral load between fully vaccinated and unvaccinated cases, with 17 studies suggesting no difference and 8 studies suggesting higher Ct values (lower viral load) in fully vaccinated cases.…”
Section: Viral Load (Ct Values)mentioning
confidence: 99%
“…In addition, the viral load data showed that only patients in the partially and fully vaccinated AstraZeneca groups had a statistically significant reduction in viral load at follow-up (8 to 12 days after COVID-19 diagnosis), compared to other vaccines and unvaccinated cases. is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) Overall, evidence from 28 studies (25 studies from the previous review (Acharya et al 2021, Chia et al 2021, Christensen et al 2022, Elliott et al 2021, Eyre et al 2022, Griffin et al 2021, Hirotsu et al 2021, Hsu et al 2021, Kale et al 2021, Kang et al 2022, Kerwin et al 2021, Kislaya et al 2022b, Levine-Tiefenbrun et al 2021a, Levine-Tiefenbrun et al 2022, Luo et al 2021a, Lyngse et al 2022b, Magalis et al 2021, Pouwels et al 2021, Puhach et al 2022, Riemersma et al 2021, Salvatore et al 2021, Servellita et al 2022, Siddle et al 2022, Singanayagam et al 2021, Yi et al 2022, and three studies from this update (Barbosa et al 2022, Migueres et al 2022, Sriraman et al 2022, suggests mixed evidence for a difference in viral load between fully vaccinated and unvaccinated cases, with 17 studies suggesting no difference and 11 studies suggesting higher Ct values (lower viral load) in fully vaccinated cases.…”
Section: Viral Load (Ct Values)mentioning
confidence: 99%
“…The reported rates range from 0.01% to 57% (in an outbreak): 0.01%, 0.05% (although later, in an outbreak they reported a rate of 57%, 0.09%, 0.2%, 0.3% 0.4%, 0.55%,1.5% and 5.5%, according to geographic location, type of people vaccinated (nursing homes, health workers, general population), time since vaccination, predominance of new variants of SARS.Cov-2, data on an outbreak, inclusion or not of asymptomatic patients, etc. [17,[51][52][53][54][55][56][57][58]. It must be taken into account that where vaccination rates are high, breakthrough cases already represent one third of all cases A situation can be envisaged in which, in the absence of third doses, breakthrough cases represent a higher number of COVID cases and the disease they cause in most cases remains relatively mild.…”
Section: Ir Of Covid-19 Breakthrough Infections In Vaccinated Peoplementioning
confidence: 99%